The “MEDiterranean International Acoustic Survey”: An introduction - GIANNOULAKI, MARIANNA; ZWOLINSKI, JUAN; CEMAL GUCU, ALI; De FELICE, ANDREA; SOMARAKIS, STYLIANOS (Mediterranean Marine Science, 2021)
Special Issue for 2021 dedicated to papers produced within the MEDIAS project. Guest editors: Marianna Giannoulaki, Juan Zwolinski, Ali Cemal Gucu, Andrea De Felice, and Stylianos Somarakis.